STUDI DESKRIPTIF KEMAMPUAN MOTORIK KASAR ANAK USIA 4-6 TAHUN (SURVEY DI RA RAUDHATUL IKHLAS BEKASI SELATAN): Motorik Kasar - Samsinah; Sofia Trisna Sazain; Sabila Nur Masturah; Edy Mustofa (Al Hanin, 2023)
ABSTRACK Children aged 5-6 years Early childhood is an individual who is undergoing a rapid development process, so that children who are still in preschool, a child's gross motor development is needed and must be done, one of which is jumping, pushing and throwing activities. Based on the results of observations that researchers have found at RA Raudhatul Ikhlas, South Bekasi, that lack of gross motor skills in the development of children walking in place, lack of development of children in jumping on one leg, lack of development of children in pushing objects, and lack of development of children in throwing. The purpose of this study is to find out how to improve gross motor skills in motor development and to know the gross motor development of children after jumping, pushing and throwing activities at RA Raudhatul Ikhlas, South Bekasi. The methodology in this study uses a quantitative approach with a descriptive method. Data collection techniques in this study were carried out through observation and documentation. Based on the results of data collection, it can be concluded that, when learning by using jumping, pushing and throwing activities, the gross motoric development of children is seen developing or increasing every meeting so that children who cannot perform simple movements become able. Children also become more excited because of the tools / materials so that children become happy and cheerful in carrying out activities. Therefore jumping, pushing and throwing at children is very important and important so that these activities can be applied from an early age.